2012
DOI: 10.1089/thy.2012.0134
|View full text |Cite
|
Sign up to set email alerts
|

RETProto-Oncogene Genetic Screening of Families with Multiple Endocrine Neoplasia Type 2 Optimizes Diagnostic and Clinical Management in China

Abstract: Our results further substantiate that gene scanning of all relevant RET exons is a powerful tool in the management of MEN2 patients, especially in asymptomatic carriers, and has led to earlier diagnosis and more complete initial treatment of patients with MEN2 in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…Outside the Western hemisphere, RET gene analysis used to be employed predominantly for molecular confirmation of clinically manifest MEN2A and 2B, for instance in Argentina (25), Iran (26), India (27), Korea (28), and China (29,30). In this setting, stronger RET mutations in codons 634 (ATA class C) and 918 (ATA class D) rule the scene (64-100%, as opposed to 45% in Continental Europe) and moderate (ATA class B) or weak (ATA class A) mutations are exceptional (Table 4).…”
Section: Geographic Distribution Of Ret Mutations Outside Europementioning
confidence: 99%
See 1 more Smart Citation
“…Outside the Western hemisphere, RET gene analysis used to be employed predominantly for molecular confirmation of clinically manifest MEN2A and 2B, for instance in Argentina (25), Iran (26), India (27), Korea (28), and China (29,30). In this setting, stronger RET mutations in codons 634 (ATA class C) and 918 (ATA class D) rule the scene (64-100%, as opposed to 45% in Continental Europe) and moderate (ATA class B) or weak (ATA class A) mutations are exceptional (Table 4).…”
Section: Geographic Distribution Of Ret Mutations Outside Europementioning
confidence: 99%
“…In this setting, stronger RET mutations in codons 634 (ATA class C) and 918 (ATA class D) rule the scene (64-100%, as opposed to 45% in Continental Europe) and moderate (ATA class B) or weak (ATA class A) mutations are exceptional (Table 4). This situation may be changing rapidly in some regions with the rollout of extensive screening programs (30).…”
Section: Geographic Distribution Of Ret Mutations Outside Europementioning
confidence: 99%
“…It has also been suggested that family members with the same RET mutation may display different clinical phenotypes, and the offspring may display earlier PHEO phenotypes [ 4 ]. Our findings also implied that MEN2-related PHEO occurrence may be affected by modifying factors from parents or the environment, and even by other mechanisms, such as errors in chromosomal replication during cell division or a second somatic mutation [ 4 ],[ 26 ]. Additionally, sufficient pre-operative preparation before PHEO is necessary and preferential PHEO excision favors the avoidance of burst hypertensive crisis caused by PHEO during MTC or other non-PHEO surgical procedures or even death [ 4 ],[ 5 ],[ 26 ].…”
Section: Discussionmentioning
confidence: 86%
“…Our findings also implied that MEN2-related PHEO occurrence may be affected by modifying factors from parents or the environment, and even by other mechanisms, such as errors in chromosomal replication during cell division or a second somatic mutation [ 4 ],[ 26 ]. Additionally, sufficient pre-operative preparation before PHEO is necessary and preferential PHEO excision favors the avoidance of burst hypertensive crisis caused by PHEO during MTC or other non-PHEO surgical procedures or even death [ 4 ],[ 5 ],[ 26 ]. Unilateral MEN2A-related PHEO patients usually show contralateral PHEO over a period of 10 years and malignant MEN2A-related PHEO is rare (0.4%-5.0%) [ 4 ],[ 27 ],[ 28 ].…”
Section: Discussionmentioning
confidence: 86%
“…Немногочисленные сообщения о двойных мутациях противоречивы в отношении по-тенциирующего влияния второй мутации на клини-ческие проявления, в том числе на возраст манифе-стации наследственного МРЩЖ и синдрома МЭ-Н2А [8,9,[11][12][13]. В ряде работ [6,9,13,[18][19][20][21][22][23] со-общается о более агрессивном течении МРЩЖ, более высокой пенетрантности феохромоцитомы, появлении ганглионейроматоза, характерного для синдрома МЭН2Б, эктопической продукции АКТГ опухолью (МРЩЖ или феохромоцитомой) у боль-ных с множественными RET мутациями. Поэтому, хотя в данном случае роль каждой мутации в отдель-ности позволяла придерживаться тактики активно-го наблюдения, наличие одновременно двух мута-ций послужило аргументом в пользу профилактиче-ской тиреоидэктомии.…”
Section: Discussionunclassified